Effect of Coleus blumei Miana Leaf Extract in Feed on Whiteleg Shrimp Immune Response - Basir, Buana; Jum’ah, Ulfatul; Rapi, Nuraeni Lewa; Kustam, Sri Rukmini (Universitas Gadjah Mada, 2025)
Coleus blumei (miana) can be used as an antimicrobial, antibacterial, antioxidant, and anti-inflammatory. Research on miana leaf extract in feed to increase the immune response of whiteleg shrimp has not been found. This study aims to analyze miana leaf extract in feed on the immune response of whiteleg shrimp. The study was conducted in July 2023 at the Hasanuddin University Laboratory and the Bogor Agricultural Institute Laboratory. The method used was a completely randomized design, 4 treatments and 3 replications, extracts of 0 g, 1 g, 2.5 g, and 7.5 g/kg of feed. The statistical results of the treatment gave a significant effect (p<0.05) on total hemocytes and phenoloxidase activity but did not give a significant effect (p>0.05) on the survival of whiteleg shrimp. The extract of 7.5 g/kg of feed had the highest impact on total hemocytes 8.43x103 cells/mm3, phenoloxidase activity 0.222 optical density ƛ=490, and 100% survival. The extract of 0 g/kg feed had the lowest impact on total hemocytes, 2.37x103 cells/mm3, phenoloxidase activity of 0.09 Optical Density ƛ=490, and survival of 90%. Conclusion, Coleus blumei leaf extract in feed can improve the immune response and survival of whiteleg shrimp. The recommended concentration in aquaculture is 7.5 g/kg.